Determinants of healthcare utilisation among the elderly in Malaysia - Mohamad Yunus, Noorain; Abd. Manaf, Noor Hazilah; Omar, Azura (2015)
Purpose: Ageing is a truly important global phenomenon that is proceeding at very fast paced in many parts of the developing world. Consequently, this trend will demand larger proportion of financial resources to be allocated for healthcare services in the future. Therefore, this study will be conducted to investigate the determinants of utilisation of healthcare services for the elderly. Design/methodology/approach: This paper is based on literature review, presents the theoretical and empirical literature on determinants of healthcare utilisation and the outcome of healthcare utilisation towards the elderly. Findings: Drawing from the past literature review, the authors argue that individual characteristics, psychosocial characteristics and health literacy contribute to the utilisation of healthcare resources of the elderly. Furthermore, the researchers discussed the impact of healthcare utilisation towards the outcomes, namely perceived health status and patient satisfaction of the elderly. Originality/value: This paper will build up upon the present knowledge by exploring the contributing factors of utilisation of healthcare services among the elderly. This paper is valuable for researchers interested in the field of healthcare utilisation. Keywords: Healthcare utilisation; Population ageing; Individual characteristics; Psychosocial characteristics; Health literacy; Health status